State and State-Sponsored Terrorism: A Case Study of Russia - Žotkevičiūtė Banevičienė, Agnietė (Politologija, 2024)
Despite the worldwide condemnation of Russia’s aggressive activities in the war against Ukraine, there is no unified definition of terrorism in relation to Russia. Russia is referred to as a terrorist state as well as a state that supports terrorism, and the conceptions of a terrorist regime or a user of terrorist methods dominate. The answer to whether Russia should be labelled a terrorist state, a state that sponsors terrorism, or possibly not designate Russia’s actions as terrorism depends on the definition of terrorism. Given the complexities of the conception of terrorism, the purpose of this article is to present a possible assessment of Russia’s aggression in Ukraine by exploring the challenge of defining state and state-sponsored terrorism in traditional and critical terrorism studies. The article promotes a wider academic discussion regarding state and state-sponsored terrorism, not only from diverse theoretical perspectives in terrorism studies but also by evaluating the issue of the phenomenon’s politicization in the context of international relations.